The continuation of clinical trials in times of war: A need to develop ethics and situationally adaptive clinical research guidelines - Kurihara, Chieko; Crawley, Francis P.; Baroutsou, Varvara; Becker, Sander; Franke-Bray, Brigitte; Granville, Courtney A.; Matsuyama, Kotone; Naseem, Shehla; Schenk, Johanna; Kerpel-Fronius, Sandor (Frontiers in Medicine, 2022)
This paper focuses on the following challenges for clinical trials in war settings: - War creates a fundamental disruption of healthcare provision, including patient access to clinical trials. - Within the context of the essential need to care for war victims and refugees, attention to ongoing and even new clinical trials may be crucial for the protection of health and the well-being of many patients. - In the current setting of the war in Ukraine, a substantial number of refugees already engaged as clinical trial participations have been transferred from sites in Ukraine to sites in other countries. - We need to revisit the principles of research ethics considering both human rights law in peace settings and humanitarian law in war or conflict settings.